Analisis Kebutuhan Pengembangan Perumahan Dan Kawasan Permukiman Kabupaten Pesisir Barat Tahun 2018 – 2037 - Fahmi; Widyawati, Ratna (Jurnal Profesi Insinyur Universitas Lampung, 2020)
The development of housing and residential areas is a basic human need that has a strategic function as a center for family education, cultural nursery, and improving the quality of future generations, and is a manifestation of identity. One of the manifestations of the achievement of people's welfare is marked by increasing the quality of a decent and dignified life through meeting the needs of boards as one of the basic human needs. Thus the development of housing and settlement areas is one of the strategic fields in the efforts of Indonesian human development as a whole and the construction of housing and settlement areas is a multi-sector activity, the results of which directly touch one of the basic needs of the community. Meeting the needs of decent housing in a healthy environment is certainly the duty of the community itself, the government in this case has the task of creating a conducive development climate so as to provide opportunities for businesses to provide housing and residential areas. The dynamics of the development of spatial use in the area of Pesisir Barat Regency has an impact on the occurrence of a shift in the use of space from areas that are characterized by rural areas to areas that are characterized by urban areas, increased growth of built areas and misuse of land allotment for settlements A backlog of houses can be measured from two perspectives, from the residential and ownership aspects. Home backlog from the perspective of occupancy is calculated by referring to the ideal calculation concept: 1 family occupies 1 house. The formula used to calculate the house backlog from the perspective of occupancy is: Backlog = ∑Family - ∑Home. The concept of inhabiting in the calculation of the backlog represents that each family is not required to own a house, but the Government facilitates / encourages that every family, especially those belonging to Low Income Communities (MBR), can inhabit decent homes, either by leasing / contracting, buying / inhabiting own house, or living in a house owned by a relative / family as long as security of residence (secure tenure) is guaranteed. Ownership backlog is calculated based on the home ownership rate / percentage of households (households) occupying their own home. The development of housing and settlements in Pesisir Barat Regency is caused by several factors that ultimately require a large amount of space in carrying out their activities. In determining the allocation of space for meeting housing needs, the number of housing needs in Pesisir Barat Regency is determined first. Determination of the needs for the number of houses up to 2037 is calculated from the population of the predicted year.